Análise de discrepâncias em pacientes acompanhados pela clínica cirúrgica de um hospital público do oeste do Paraná - Baldin, Simona Renz (2019)
Several mistakes concerning medications have occurred due to a failure to obtain the patient's history on medicine use and his changing care levels. Thus, it was necessary to analyze patients’ discrepancies that were hospitalized and observed by the surgical clinic in a public hospital of Paraná. A prospective cross-sectional study was carried out from February to May 2018, based on a structured interview. Discrepancies were registered in medications that patients took at home, which were prescribed during their hospitalization. Therefore, it was observed that one hundred patients were analyzed and fifty-nine presented at least one discrepancy. Most of them were female (68%), with an average of 55.7 years old. A percentage of 78.9% by default of the fifty-seven unintentional discrepancies was recorded. This study has shown a high rate of discrepancy on prescriptions, suggesting the importance of a pharmacist on taking part of a multi-professional team to contribute to patient’s safety.